Efficiency Reformulation of Ministry/Agency Budget Performance - Herawaty Tetty Sudarminto (Yayasan Riset dan Pengembangan Intelektual, 2023)
Budget performance evaluation is an assessment process carried out on budget implementation in order to measure the extent to which the performance of the organization or program funded by the budget has been achieved. Budget performance evaluation aims to evaluate the effectiveness, efficiency, and accountability of budget implementation and assess the extent to which the goals and objectives have been set are achieved. One of the variables used to measure Budget Performance Evaluation (EKA) is the efficiency variable where this variable is obtained from measuring budget allocations, budget realization and achievement of detailed outputs. This article aims to find out whether treatment modifications with various scenarios can maintain efficiency values and to analyze the ideal calculation formula for efficiency variables. The research method used in this study is a mixed method where the analysis simulates the data in the efficiency formula by changing the numbers in the output indicator realization, output indicator target, budget allocation and budget realization. From the simulation results, it can be concluded that there are inconsistencies in the results obtained from the efficiency figures produced. The implications of the resulting inaccuracies will affect the value of budget performance to be inaccurate and not following the reality in the field. So that it will have a biased impact when giving intensive or budget reductions on the budget performance of ministries/institutions.